Deeper investigation on methane generation from synthetic wastewater containing oxytetracycline in a scale up acidic anaerobic baffled reactor. (August 2021) - Li, Chunxing; Wang, Ruming; Yang, Xiaoyong; Zhou, Mingdian; Pan, Xiaofang; Cai, Guanjing; Zhang, Yifeng; Zhu, Gefu
Graphical abstract: Highlights: Scale up anaerobic baffled reactor was used for treating oxytetracycline wastewater. Methane was generated under acidic condition with pH of 4.60. Chemical oxygen demand and oxytetracycline removal efficiencies reached 95% and 60% Oxytetracycline addition significantly changed the microbial community. Methanosaeta dominated the archaea community under acid condition. Abstract: Acidic anaerobic digestion attracted much attention and interest due to its significant advantage in wastewater treatment. In the present study, methanogenic fermentation was successfully operated under acidic condition during treating wastewater containing oxytetracycline (OTC) in a scale up anaerobic baffled reactor (ABR). After start-up process, the pH value in the first compartment was 4.60 with high activity of methanogenesis. After stabilization, different OTC loading of 1.0, 3.3 and 5.0 g/m 3 /d was added in the influent for OTC removal. The resulted showed that OTC addition had little impact on the methane generation with whole COD and OTC removal rate of 95% and 60%, respectively. The microbial analysis, OTC addition could significantly influence the bacteria and archaea communities. To be more specific, Methanosaeta showed the highest relative abundance and tolerance to OTC under acidic condition. The present work supplied deeper insights into methane generation from acidic condition during wastewater containing OTC treatment.